The Juridical Implications of Designating Cultural Heritage Areas on Spatial Utilization and Natural Resource Utilization - Bagas Hega Samudra; Agus Sekarmadji (IHSA Institute, 2023)
Mount Penanggungan is a sacred mountain in East Java with rich cultural wealth, including archaeological sites from the Hindu-Buddhist era that have been legalized by the decree of the Governor of East Java No. 188/18/KPTS/013/2015 then improved by the decree of the Governor of East Java No. 188/627/KPTS/013/2017. However, sand mining activities in the area have the potential to damage cultural heritage and the environment. This study explores the legal framework for protecting cultural heritage areas, including regulations and duties assigned to the government/local governments. The study also identifies three main problems that hinder the implementation of the law: legal substance, legal structure/institution, and legal culture. Despite the existence of laws, sand mining activities continue because of the community’s dependence on the economy, imbalance of legal overlap, and low legal awareness among government officials and the community. To overcome these problems, this study recommends improving legal substance, legal structure/institution, and legal culture through education, counseling, role modeling, and law enforcement. More comprehensive protection and law enforcement are needed to preserve cultural heritage. This study contributes to the understanding of the legal framework for protecting cultural heritage areas and provides recommendations to the government to implement the law effectively